PENYELESAIAN KREDIT MACET YANG TERJADI PADA KREDIT USAHA KECIL INFORMAL PADA PT.BPR KHATULISTIWA BONJOL KANTOR PUSAT DI KECAMATAN LUBUK SIKAPING KABUPATEN PASAMAN PROVINSI SUMATERA BARAT - Hendrico Rahmat; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Banking institutions is a financial intermediary, which means that banks can obtainfunds from the parties that have many funds are then channeled to those who need funds.Once the magnitude of the role of money in meeting the needs, ways to earn money as asource of revenue through the proposed loans to banks and other financial institutions. RuralBank business one of which is providing credit, the practice of granting credit to customersthere are problems facing the bad credit. PT.BPR Khatulistiwa Bonjol has some kind ofcredit one of them is an informal small business loans, small business loans are used byborrowers to informal working capital or investment, which is beneficial to the debtor. In theinformal small business lending to customers there are problems of bad loans made bycustomers PT.BPR Bonjol Equator and needed resolution.The purpose of this thesis How does the process of resolving the bad debt problemthat occurs in informal small business loans on the PT.BPR Khatulisitwa Bonjol snag in thedistrict headquarters Lubuk Sikaping, Are the factors that cause bad credit happens to smallbusiness loans in the informal PT.BPR Khatulisitiwa Bonjol headquarters in district LubukSikaping, What are the obstacles that occur in the process of settlement of bad loans whichoccur in informal small business loans on the PT.BPR Khatulistiwa Bonjol snag in thedistrict headquarters Lubuk SikapingFrom this research it can be concluded that the first step taken by PT.BPRKhatulisitwa Bonjol in dealing with bad loans that occurred in informal small business loansis sending warning letters, perform settlement, sells credit guarantee is the latest step takenby PT.BPR Khatulisitiwa Bonjol, factors that cause bad credit happens to small businessloans in PT.BPR Khatulisitwa Bonjol informal headquarters in the District Lubuk Sikaping isabusing Debtor informal small business loans, impaired health Debtor, Debtor less able tomanage credit in developing, the debtor's bad faith in the resolution of bad debts, barriersthat occur in the process of settlement of bad loans which occur in informal small businessloans on the Equator PT.BPR snag in the district headquarters Lubuk debtor Sikaping is badfaith, the Equator PT.BPR Bonjol must be able to draw up a mature and predictable planningcarefully for the future business prospects of the debtor, the debtor in order to have a highawareness to fulfill its obligations to the bank and the debtor perform well before bank loansto the debtor should be able to estimate whether the development effort can pay the loancredit.Keywords: -Settlement -Bad credit -Informal small business loans